GPS availability and positioning issues when the signal paths are aligned with ionospheric plasma bubbles - Moraes, Alison de O.; Vani, Bruno C.; Costa, Emanoel; Abdu, Mangalathayil A.; de Paula, Eurico R.; Sousasantos, Jonas; Monico, João F. G. [UNESP]; Forte, Biagio; de Siqueira Negreti, Patrícia Mara; Shimabukuro, Milton Hirokazu [UNESP] (Springer Nature, 2018)
The propagation paths of signals through equatorial ionospheric irregularities are analyzed by evaluating their effects on Global Navigation Satellite System (GNSS) positioning and availability. Based on observations during 32 days by a scintillation monitor at São José dos Campos, Brazil, it was noted that there is a dominance of enhanced scintillation events for Global Positioning System (GPS) ray paths aligned with the azimuth angle of 345° (geographic northwest). This azimuth corresponds to the magnetic meridian that has a large westward declination angle in the region (21.4ºW). Such results suggest that the enhanced scintillation events were associated with GPS signals that propagated through plasma bubbles aligned along the direction of the magnetic field. It will be shown that, under this alignment condition, the longer propagation path length through plasma bubbles can result in more severe scintillation cases and more losses of signal lock, as supported by proposed statistics of bit error probability and mean time between cycle slips. Additionally, large precise positioning errors are also related to these events, as demonstrated by precise point positioning experiments.
Keywords: Fading distribution; GPS availability; Ionospheric scintillation